Dampak Sosial Media Marketing, Daya Tarik dan Kepuasan terhadap Minat Berkunjung Kembali di Desa Wisata Kabupaten Bangkalan - AS, Fathor; Rizki (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine the effect of social media marketing, attractiveness and tourist satisfaction on interest in visiting again in the tourist village of Bangkalan Regency. The research approach used is quantitative causality. The population consists of tourists who are currently or have visited. The sample size was 120 people. And the sampling technique used is purposive sampling. The data was collected by distributing questionnaires and the results were analyzed using the partial least squares method. The results of the study stated. Social media marketing has a positive and significant effect on tourist satisfaction. Social media marketing has a positive and insignificant effect on interest in visiting again. Attractiveness has a positive and significant effect on tourist satisfaction. Attractiveness has a positive and significant effect on interest in visiting again. Tourist satisfaction has a positive and significant effect on interest in visiting again. Keywords: Social Media Marketing, Attraction, Satisfaction, Interest in revisiting.